(untitled) (Saúde Ética & Justiça, 2013)
In populations where there is a high degree of admixture, as in Brazil, the sole use of ethnicity self-declaration information is not a good method of ethnic classifi cation. We evaluate the relationship between self-declared ethnicities with genomic ancestry and mitochondrial haplogroups in 492 individuals from Southeastern Brazil. Mitochondrial haplogroups were obtained by analyzing the hypervariable regions of mitochondrial DNA (mtDNA) and genomic ancestry was obtained using 48 autosomal ancestry informative markers (AIM). Of the 492 individuals, 74.6% self-declared as white, 13.8% as Brown and 10.4% as Black. In relation of mtDNA haplogroups, 46.3% presented African mtDNA and the major genomic ancestry was European (57.4%). When we performed the distribution of mtDNA and genomic ancestry according to the self-declared ethnicities, from 367 individuals self-declared white, 37.6% showed African mtDNA, and had a higher contribution of European ancestry (63.3%). The 68 individuals self-declared brown, 25% showed Amerindian mtDNA and few differences in the averages contribution of European and African ancestries. Those 51 subjects self-declared black, 80.4% had African mtDNA and the main contribution of African ancestry (55.6%). The Brazilian population had a very uniform degree of Amerindian genomic ancestry, and only by using genetic markers (autosomal and mitochondrial) we were able to capture this information. Epidemiological studies should use the association of these methods to provide complementary information.